Writing Citation Techniques in Writing Research Article on Scholar vs ScienceDirect Website - Ananta Thoriq Arrazi Nasution; Hansen Octavian Zendrato; Rita Hartati (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Academic literacy requires the use of citation techniques. It will authenticate research, acknowledge the original authors, and assist readers in locating additional reading materials. The citation styles of authors and scholars who publish on ScienceDirect and Google Scholar are examined in this study. Five research papers from each of these platforms are examined in our analysis, which focuses on the three primary citation strategies—direct quotation, paraphrase, and description that are outlined in Wang's framework (Wang, 2006). Our analysis reveals that while both platforms effectively employ these tactics, there are discernible differences in their implementation. Specifically, ScienceDirect papers tend to have more seamless citation integration, which enhances readability and coherence. The ScienceDirect articles do a great job of contextualizing direct quotes, simplifying complex ideas, and providing in-depth descriptive analyses that improve understanding without disrupting the flow. This research significantly advances writing abilities by determining the best practices for integrating citations into academic discourse. It highlights the need of considering platform-specific considerations when writing academic publications, particularly for researchers who are not native English speakers, and how understanding how different citation styles impact readability and coherence facilitates scholarly writing.